APPLICATION OF VALUE CLARIFICATION TECHNIQUE (VCT) IN ISLAMIC RELIGIOUS EDUCATION TO INCREASE INTERFAITH TOLERANCE AWARENESS - Mega Nurwahyuni (Education Studies and Teaching Journal (EDUTECH), 2025)
This study aims to systematically examine the implementation of Value Clarification Technique (VCT) in learning Islamic Religious Education (PAI) through the Systematic Literature Review (SLR) approach. The background of this study is based on the urgency of strengthening value education amidst the challenges of globalization, the moral crisis of the younger generation, and the need for methods that are able to internalize religious values in a meaningful way. By utilizing data from Google Scholar, DOAJ, and Scopus, 25 relevant studies were analyzed using the PICOC-PRISMA criteria. The results showed that the application of VCT in PAI covered a variety of materials (Akidah Akhlak, Fikih, SKI, Al-Qur'an Hadis), education levels (elementary to senior high school), as well as value integration strategies through reflective discussion, value selection, and moral decision-making. In general, VCT is proven effective in shaping value awareness, increasing empathy, and building students' tolerance and social responsibility. Although there are still limitations in the aspect of quantitative evaluation of attitudes, the trend of applying VCT shows a positive direction in improving the quality of holistic PAI learning.